Loperamide Induced Torsades de Pointes: A Case Report and Review of the Literature. (18th February 2016) - Mukarram, O.; Hindi, Y.; Catalasan, G.; Ward, J.
Abstract : Abuse of over the counter drugs often gets overlooked by health care providers. Loperamide is one such over the counter drug that is often abused by drug addicts. We present here a case of a young male attaining euphoria from taking massive doses of loperamide. He developed Torsades de Pointes and subsequent cardiac arrest. We found similarities in the progression of myocardial electrical conduction abnormalities among loperamide and other previously known arrhythmogenic drugs. We intend to raise concern over the ease of availability of such drugs over the counter and increase the index of suspicion for over the counter drug abuse from our experience.